Simulación de análisis dinámicos de membranas electrohiladas de ácido poliláctico (PLA) con grafeno - Bohórquez Castañeda, José Santiago (Universidad Antonio Nariño, 2021)
In this study we performed simulations of stress tests, vibrations with natural frequencies and fatigue, as well as analysis of electrical tests of electrolyzed polylactic acid membranes (PLA) with graphene, in order to determine whether the addition of different percentages of microparticles presented alterations in the electrical and mechanical properties of the material. For the simulation we used the software of Autodesk Inventor and the module Nastran In Cad, this was with analysis of data of electrical tests carried out with Megger and of sustained voltage made in laboratories of the UPTC headquarters Duitama and bibliographic review of previous studies. The result of the simulation leads to the conclusion that the percentage of graphene reinforcement influences the mechanical and electrical properties of the membrane, decreasing the electrical resistance of the membrane and the decrease in the ultimate tensile strength, response to sine frequencies and life in cycles against fluctuating loads.